Analisis Pengaruh Pengeluaran Pemerintah dan Tenaga Kerja terhadap Produk Domestik Regional Bruto di Provinsi Jawa Timur Tahun 2014-2018 - Rofiq, Ainur (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2020)
This research was conducted to determine the effect of government spending and labor on economic growth in East Java Province in 2014-2015. The results showed that government expenditure, labor had a positive and significant effect on Gross Regional Domestic Product (GRDP). Simultaneously, government and labor expenditures affect the Gross Regional Domestic Product (GRDP)